2005
DOI: 10.1161/01.res.0000172081.30327.28
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Apoptosis-Inducing Factor in Harlequin Mutant Mice Sensitizes the Myocardium to Oxidative Stress–Related Cell Death and Pressure Overload–Induced Decompensation

Abstract: Abstract-Apoptosis-inducing factor (AIF), or programmed cell death 8 (Pdcd8), is a highly conserved, ubiquitous flavoprotein localized in the mitochondrial intermembrane space. In vivo, AIF provides protection against neuronal apoptosis induced by oxidative stress. Conversely, in vitro, AIF has been demonstrated to have a proapoptotic role when, on induction of the mitochondrial death pathway, AIF translocates to the nucleus where it facilitates chromatin condensation and large scale DNA fragmentation. To dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
101
1
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 44 publications
5
101
1
2
Order By: Relevance
“…The Hq hearts also showed more damage from ischemia-reperfusion and aortic banding-induced heart failure. They provided data showing that AIF deficiency reduced the ability of cardiac mitochondria to decompose hydrogen peroxide, suggesting that AIF may function as a cardiac antioxidant independent of mitochondrial complex activity [25]. A subsequent study [26] substantiated the suggestion that AIF functions as an important cardiac free radical scavenger by showing that EUK-8, a superoxide dismutase and catalase mimetic, protected against pressure overload-induced heart failure in AIF-deficient Hq mice.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The Hq hearts also showed more damage from ischemia-reperfusion and aortic banding-induced heart failure. They provided data showing that AIF deficiency reduced the ability of cardiac mitochondria to decompose hydrogen peroxide, suggesting that AIF may function as a cardiac antioxidant independent of mitochondrial complex activity [25]. A subsequent study [26] substantiated the suggestion that AIF functions as an important cardiac free radical scavenger by showing that EUK-8, a superoxide dismutase and catalase mimetic, protected against pressure overload-induced heart failure in AIF-deficient Hq mice.…”
Section: Discussionmentioning
confidence: 94%
“…Joza et al showed that animals that were cardiac and skeletal muscle-specifically deficient in AIF developed severe dilated cardiomyopathy, heart failure, and skeletal atrophy accompanied by impaired activity and protein expression of respiratory chain complex I, defective mitochondrial respiratory function, a metabolic switch toward glucose metabolism, and lactic acidosis. Van Empel et al [25] demonstrated that cardiomyocytes isolated from Hq mice, an AIF-deficient mouse mutant, were more sensitive to hydrogen peroxide-induced cell death. The Hq hearts also showed more damage from ischemia-reperfusion and aortic banding-induced heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…8 Knockdown, deletion or hypomorphic mutation of AIF (the harlequin or Hq mutation) reduces the expression of complex I subunits in the respiratory chain, 8 thereby provoking a mitochondriopathy that leads to progressive neurodegeneration, photoreceptor loss and cardiomyopathy. [9][10][11][12][13] The consistent finding that the targeting of AIF mostly affects the central nervous system (CNS) 9 might either be explained by the general tendency of complex I mitochondriopathies to manifest at the level of the CNS 14 and/or by an implication of AIF in the differentiation of neuronal cell precursors. 12 On apoptotic stimuli, AIF, which is able to directly interact with DNA, 15 translocates to the nucleus and participates in chromatin condensation and chromatinolysis.…”
mentioning
confidence: 99%
“…20 In mice, the Hq mutation has been shown to reduce acute neuronal cell death after ischemia, hypoglycemia and neurotrauma in young animals, before they manifest the Hqassociated neurodegeneration. 21 However, the Hq mutation had no cardioprotective effect 13 and was not able to make islet beta cells more resistant to hydrogen peroxide-induced cell death, 22 suggesting that AIF contributes to lethal signaling in a cell type-specific manner.…”
mentioning
confidence: 99%
“…I/R induces translocation of d-protein kinase C (dPKC; the redox sensitive PKC isoform) to cardiac mitochondria, preventing pyruvate dehydrogenase reactivation (via phosphorylation of the aE1 subunit of pyruvate dehydrogenase [PDH] via PDH kinase 2) [25]. Apoptosis-inducing factor is a ubiquitous flavoprotein localized in the mitochondrial intermembrane space that is important in protecting against peroxide injury in heart [26]. Oxidant tolerance of myocytes (made inflammatory by I/R) is dependent on induction of manganese superoxide dismutase (Mn-SOD) and endothelial nitric oxide synthetase (eNOS) [27].…”
Section: Perioperative Physiologymentioning
confidence: 99%